Computer graphics and vision labs in Argentina - De Giusti, Armando Eduardo
This article describes the Computer Graphics and Vision research that are being developed by three universities’ laboratories in Argentina: III-LIDI Institute of Computing Research at National University of La Plata, VyGLab Visualization and Computer Graphics Laboratory at South National University, and CGLab Computer Graphics Laboratory at National University of San Luis.